1988
DOI: 10.1128/mcb.8.4.1489
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of hybrid dysgenesis-induced derivatives of a P-element allele at the vg locus.

Abstract: Secondary and tertiary derivatives of a P-element insertion allele at the vestigial (vg) locus were induced by hybrid dysgenesis. The derivatives were characterized by Southern analyses and, in four cases, by DNA sequencing. The alterations found were P-element internal deletions, deletions of the insert and/or adjacent vg region DNA, or novel insertions of P-element sequences into existing P-element inserts. The relatively high frequency of secondary insertions into P-element sequences observed herein is unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The rosy gene in the repair structures was fully functional, as demonstrated by the ability of the fly lines to grow on purine-supplemented media (7) and by the ability of the rosyϩ gene on the P{yellowϩ rosyϩ} template to complement a homozygous ry 506 allele. This experiment demonstrated that internal conversions at the white gene do not require template white gene homology, in agreement with findings at other loci (21,22,55,61).…”
Section: Fig 2 Structure Of the Starting Components The Wsupporting
confidence: 78%
See 1 more Smart Citation
“…The rosy gene in the repair structures was fully functional, as demonstrated by the ability of the fly lines to grow on purine-supplemented media (7) and by the ability of the rosyϩ gene on the P{yellowϩ rosyϩ} template to complement a homozygous ry 506 allele. This experiment demonstrated that internal conversions at the white gene do not require template white gene homology, in agreement with findings at other loci (21,22,55,61).…”
Section: Fig 2 Structure Of the Starting Components The Wsupporting
confidence: 78%
“…Another possible repair event, suggested to us by Ross Hodgetts, would be those in which the P{walLy} template P ends exactly replace those of the P-w hd element. These replacements have been observed by other groups and have been referred to as targeted transpositions (17,21,22,56,61). The predicted structures of these events are shown in Fig.…”
Section: Fig 2 Structure Of the Starting Components The Wmentioning
confidence: 96%
“…In y76d28 and y+3"11, the inserted P element is in the opposite transcriptional orientation relative to the y gene. RNA analysis showed that both flies produce a 1.9-kb RNA whose size and developmental expression are indistinguish- (13).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which these P insertions affect gene expression are not well established. In at least one case, transcriptional interference has been implicated (13).…”
mentioning
confidence: 99%
“…Because a transposon inserted within a gene is flanked by portions of that gene, probes derived from the transposon can be used to retrieve portions of the gene that it has inactivated. Many genes from a wide variety of organisms have already been isolated in this manner, including thepallida locus of snapdragon (Martin et al, 1985), the bronze locus of maize (Fedoroff et al, 1984), the unc-22 locus of Caenorhabdiris elegans (Moerman et al, 1986), and the vestigial locus of Drosophila (Williams et al, 1988). In theory, any gene whose inactivation leads to a discernible phenotype may be tagged and cloned by using transposons.…”
Section: Introductionmentioning
confidence: 99%